POTENSI DAN TANTANG PEMBIBITAN KARET DI PROVINSI JAMBI - ., Yardha; Meilin, Araz (Jurnal Agroekoteknologi, 2009)
ABSTRACTRubber replanting in Jambi Province started from 2006 to 2010 need millions high quality of rubber clon every year. Assesment was aimed to describe a potency of rubber seedling in every year mucipal in Jambi Province. Assesment was done in three month Maret to June 2006 in Tebo, Merangin, Sarolangun and Muaro Jambi by survey, interview with questioner of state breeder of rubber estate. Respondences were selected by purposive sampling. Result show each municipal has already TRUP. Quantity rubber seed was enough produced to fulfill their own need. Treat was occurred due to aviabilitty of entress, hence it needs a supply from other breeding places.Key words: High quality of rubber clon, Breeder, Entres, TRUP